Beverage consumption and anthropometric outcomes among schoolchildren in Guatemala - Makkes, Sabine (Matern Child Nutr, 2010)
This analysis explores the clustering of beverage patterns in a single day in private vs. public school children in urban Guatemala. This study is based on measurements taken from 356 third‐ and fourth‐grade pupils from the highland city of Quetzaltenango. Height, weight and body mass index were assessed, and one day's intake of all foods and beverages using a pictorial workbook and dietician assisted recall. Mean differences in beverage consumption were compared for private vs. public school children and by anthropometric outcomes (stunting, overweight and obesity). Plain water was consumed by 30.9% of the children on the day intakes were measured, with higher proportions of water drinkers among private school children. Children having reported water intake on that day consumed 154 fewer kcal (−7.7%) compared with the energy intake of children not having reported water intake (P = 0.02). Significantly more children of high socio‐economic status (SES) consumed dairy, fruit juice, commercial fruit juice, fruit drink and soda whereas low SES children consumed thin gruels and infusions. A key result from this study is the finding of a lower energy intake shown by children reporting water intake.